KOMPETENSI ARBITRASE INTERNASIONAL DAN PENGADILAN NASIONAL TERKAIT PENYELESAIAN SENGKETA PENANAMAN MODAL ASING - Geraldi, Aldo Rico (Jurnal Advokasi, 2017)
This research aims to analyze the competence of international arbitration and national courts that was related to the dispute of foreign investment disputes. This research is a normative law research conducted by collecting legal material. The results of this study indicate that the settlement of investment disputes by way of litigation or trial has final legal force, while arbitration guarantees and protects the credibility of a business which is run and produces a win-win solution. Furthermore, regarding the Singapore International Arbitration Center (SIAC) is an independent non-profit organization that prioritizes justice and transparency. SIAC may arrange arbitration under other rules agreed by the parties, has an accredited arbitrator panel comprising of regional panels and international panels and has arbitrators for ad hoc arbitration.